PENGARUH JOB CRAFTING, MINDFULNESS DAN SOCIAL SUPPORT TERHADAP KINERJA KARYAWAN PT. PERKEBUNAN NUSANTARA 1 REGIONAL 4 SURABAYA - Filayati, Gilang; Tandiyono, Tan Evan (GEMAH RIPAH: Jurnal Bisnis, 2025)
This study aims to analyze and prove the influence of Job Crafting, Mindfulness and Social Support variables simultaneously on employee performance at PT Perkebunan Nusantara I Regional IV Surabaya. The population in this study were employees of PTPN I Regional IV Surabaya with 46 samples. Using quantitative methods and carried out by testing the SPSS 26 program. The analysis technique used was multiple linear regression analysis, hypothesis testing using the T test and F test, while other testing techniques used validity, reliability, normality, multicollinearity and heteroscedasticity tests and the coefficient of determination (R2). The results of this study indicate that partially the Job Crafting variable has a positive and significant effect on employee performance, the Mindfulness and Social Support variables have a positive and significant effect on employee performance. While simultaneously Job Crafting, Mindfulness and Social support have a significant effect on employee performance at PT Perkebunan Nusantara I Regional IV Surabaya. While the results of the coefficient of determination (R2) test state that the influence of job crafting, mindfulness and social support on employee performance is 80,3% while 19,7% is influenced by other variables outside the type of research studied.